Effect of Michelia champaca Linn on pylorous ligated rats - A. R. Mullaicharam, M. Surendra kumar (Journal of Applied Pharmaceutical Science)
it is main species of Michelia used for the treatment of gastric ulcers. However, there have been no reports regarding the anti-ulcer activity of Michelia champaca Linn extracts. Therefore, this study was carried out to evaluate the anti-ulcerogenic property of the alcoholic and aqueous extracts of leaves and flowers of Michelia champaca Linn. The anti-ulcer assays were performed using nonsteroidal anti-inflammatory drug (NSAID)- aspirin induced ulcer. The effects of the extracts on gastric content volume, pH, total acidity, ulcer index and stomach using the pylorus ligated model were evaluated at a dose of 300mg/kg. In the aspirin induced ulcer model, it was observed that the treatment with Michelia champaca Linn extracts significantly reduced the gastric juice, total acidity, ulcer index and elevation in gastric pH. The results were comparable with the positive control cimetidine 50mg/kg. Further the results were confirmed using histopathological studies of the stomach. These results showed the anti-ulcerogenic property of Michelia champaca Linn extracts. The maximum efficacy was shown by the flower aqueous extract followed by leaf alcoholic, flower alcoholic and leaf aqueous extracts.
Keywords: Michelia Champaca Linn , Pylorous Ligation, Antiulcer.